2015
DOI: 10.2174/1871527315666151111124937
|View full text |Cite
|
Sign up to set email alerts
|

Whole body vibration training improves walking performance of stroke patients with knee hyperextension: a randomized controlled pilot study

Abstract: The results suggest that 8 weeks whole body vibration training can reduce knee hyperextension and increase ambulatory speed in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Among them, 256 and 161 were male and female patients, respectively; the sex for 30 participants was not specified. 38 Average age of the participants ranged from 53.8 to 74.5 years (Table 1). People with both ischemic and hemorrhagic stroke were included ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 256 and 161 were male and female patients, respectively; the sex for 30 participants was not specified. 38 Average age of the participants ranged from 53.8 to 74.5 years (Table 1). People with both ischemic and hemorrhagic stroke were included ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Literature search, study characteristics and quality assessment Among the 8 studies included here, 3 studies report 6MWT distance [11,14,22], 4 studies report TUG test [11,13,14,17], 2 studies report Fugl-Meyer assessment [17,18], three studies report Berg Balance Scale [14,17,22], and 2 studies report ABC scale [11,22]. The detail for risk of bias tool are shown in ▶ fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the efficacy of whole-body vibration on functional improvement has not been well established. Several studies report the conflicting results [11,12,[16][17][18]. With accumulating evidence, we therefore perform a systematic review and meta-analysis of RCTs to investigate the efficacy of whole-body vibration versus sham procedures for stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies showed beneficial long-term effects of 4-6 weeks SS-WBV with vibration frequencies of 15-40 Hz on balance performance in individuals with stroke [ 28 , 39 , 40 , 87 , 88 ]. Regarding gait performance, Guo et al [ 89 ] reported improvements in gait speed after an 8-week SS-WBV training in individuals with stroke.…”
Section: Discussionmentioning
confidence: 99%